Socio-Economic Factors of Empowerment in Developing Countries - Khan, Rabnawaz; Xinxin, Jin; Kong, Yusheng; Cobbold, Emmanuel Yamoah (Asian Journal of Economics and Empirical Research, 2020)
The study is carried to identify the main socio economic cultural and political view determinants of women empowerment in the developing countries. The highest determination of the study is to analyze and identify the variables through which the process of women empowerment can be measured. This study is based on secondary data and reported to analyze the empowerment factor of women in 124 developing countries, the data was ordinal in nature and randomly selected from the population. The main investigation of this research study to analyzed the relationship of women fertility, socio-economic and political factor on the women empowerment. After conducting a cross sectional study for the most recent period, the findings of study show that the main deterrents towards women disempowerment are attributed as high fertility rates, high maternal mortality, gender inequality, lack of female’s access towards education, health and economic opportunities, lack of leadership and decision making qualities. It is found that a patriarchal culture is equally responsible for women in sufferings and disempowerment. However, democracy and democratic culture can contribute well in upgrading the process of women empowerment in developing countries.